2005
DOI: 10.4049/jimmunol.174.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Enhances CD95-Ligand Gene Expression in T Lymphocytes

Abstract: Hyperthermia represents an interesting therapeutic strategy for the treatment of tumors. Moreover, it is able to regulate several aspects of the immune response. Fas (APO-1/CD95) and its ligand (FasL) are cell surface proteins whose interaction activates apoptosis of Fas-expressing targets. In T cells, the Fas-Fas-L system regulates activation-induced cell death, is implicated in diseases in which lymphocyte homeostasis is compromised, and plays an important role during cytotoxic and regulatory actions mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 66 publications
1
29
1
Order By: Relevance
“…Alterations in CD95 receptor and ligand expression could contribute to the hyperthermia-induced sensitization and it has been reported that long-term hyperthermia increases the expression of CD95L (47). CD95 was similarly expressed on the surface of control and hyperthermia-exposed primary T lymphocytes ( Fig.…”
Section: Hyperthermia Sensitizes Primary Human T Lymphocytes To Apoptmentioning
confidence: 88%
See 2 more Smart Citations
“…Alterations in CD95 receptor and ligand expression could contribute to the hyperthermia-induced sensitization and it has been reported that long-term hyperthermia increases the expression of CD95L (47). CD95 was similarly expressed on the surface of control and hyperthermia-exposed primary T lymphocytes ( Fig.…”
Section: Hyperthermia Sensitizes Primary Human T Lymphocytes To Apoptmentioning
confidence: 88%
“…The levels of c-FLIP are reduced upon hyperthermia also earlier during T lymphocyte activation (days 1-3), but not to the extent that would allow triggering of the apoptotic signal, because the c-FLIP quantities are much higher at this time point (data not shown). Interestingly, Cippitelli et al (47) recently showed that long-lasting hyperthermia increases CD95L expression during T cell activation. We were not able to detect such changes in the CD95L levels in Jurkat cells during shorter hyperthermia treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, whether this reflects a direct transcriptional function for HSF-1 at the level of the FasL promoter remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…21 One study also implicated hyperthermic stress in the transcriptional regulation of FasL in activated T cells to mediate enhanced cytotoxicity of Fas-bearing target cells. 22 Elevated temperature can also impact on the Fas/FasL signaling pathway through its suppression of FLIP levels 23 and expression of a dominant active form of HSF-1 has been reported to elevate sensitivity to Fas-mediated killing, 24 but whether this reflects a simultaneous regulation of FasL levels is unclear. Furthermore, gld mice, lacking functional FasL exhibit a decreased sensitivity to heat shock-induced death.…”
mentioning
confidence: 99%